Evaluation of the expression pattern of TIAs pathway genes in response to tryptophan amino acid treatment and drought stress in Catharanthus roseus - Farshid Yousefi; Alireza Abdali Mashhadi; Amin Lotfi Jalal Abadi; Alireza Shafeinia; Saied Jalily; Narges Soltani (PLoS ONE, 2025)
The leaves of the medicinal-ornamental plant Catharanthus roseus serve as the exclusive source of the anticancer alkaloids vinblastine and vincristine. The limited synthesis of these alkaloids, alongside efforts to enhance their production, has consistently been a focal point of research. Water scarcity, recognized as one of the most significant constraints in agriculture, has prompted this study to examine the effects of the amino acid elicitor tryptophan and drought stress on the alterations in secondary metabolites of C. roseus and the genes implicated in their biosynthetic pathways. This investigation was factorial experiment conducted within a completely randomized design (CRD) with three replications. The first factor involved drought stress (40% and 100% field capacity), the second factor pertained to tryptophan concentrations (0 and 250 ppm), and the third factor encompassed duration (24, 48, 72, and 168 hours). Key genes associated with four metabolic pathways, phenolic/flavonoid, indole, terpenoid, and alkaloid pathways, were analyzed using quantitative polymerase chain reaction (qRT- PCR). Notably, the Cm gene (phenolic/flavonoid pathway) exhibited increased expression across all treatments, with the highest expression level recorded at 168 hours under the combined conditions of tryptophan and drought. Genes associated with the indole alkaloid pathway (As and Tdc) demonstrated similar temporal variations, with peak expression levels observed at 24 hours, particularly under drought stress. Genes within the terpenoid pathway (Sls) and alkaloid pathway (Str, Dat, Prx) displayed an initial increase in expression at 24 hours, followed by a decline at 48 and 72 hours, and a subsequent increase at 168 hours post-treatment in comparison to the control. Additionally, alkaloid accumulation (vincristine, vinblastine) significantly increased, especially under severe drought stress, correlating with the observed gene expression patterns. Non-enzymatic antioxidants, including phenols and flavonoids, also exhibited elevated levels in response to stress and tryptophan treatment. Furthermore, tryptophan application resulted in a doubling of plant biomass compared to the control. Collectively, the findings of this study suggest that the combination of drought stress and tryptophan application modulates gene expression and metabolite production in C. roseus, which may be crucial for optimizing alkaloid biosynthesis under drought stress conditions.